2020
DOI: 10.3390/pharmaceutics12060509
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Artemisone for the Treatment of Schistosomiasis: Formulation Challenges and In Vivo Efficacy

Abstract: Artemisone is an innovative artemisinin derivative with applications in the treatment of malaria, schistosomiasis and other diseases. However, its low aqueous solubility and tendency to degrade after solubilisation limits the translation of this drug into clinical practice. We developed a self-microemulsifying drug delivery system (SMEDDS), which is easy to produce (simple mixing) with a high drug load. In addition to known pharmaceutical excipients (Capmul MCM, Kolliphor HS15, propylene glycol), we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Likewise, Steyn et al report that absorption of dissolved ART from their "Pheroid TM " delivery system in a mouse is almost five-fold higher than from a drug suspension (18). Furthermore, for the treatment of schistosomiasis in mice, we found that 40 mg/kg per dose was sufficient if ART was dissolved in our SMEDDS (15), while to obtain similar results with a suspension required 400 mg/kg of the drug (19).…”
Section: Downloaded Fromsupporting
confidence: 68%
See 4 more Smart Citations
“…Likewise, Steyn et al report that absorption of dissolved ART from their "Pheroid TM " delivery system in a mouse is almost five-fold higher than from a drug suspension (18). Furthermore, for the treatment of schistosomiasis in mice, we found that 40 mg/kg per dose was sufficient if ART was dissolved in our SMEDDS (15), while to obtain similar results with a suspension required 400 mg/kg of the drug (19).…”
Section: Downloaded Fromsupporting
confidence: 68%
“…Consequently, it has a longer t 1/2 in vivo and is about 3-5 times more active than artesunate, in vitro and in vivo (4,7). ART toxicity has not been extensively evaluated in vivo but we have not seen any immediate effects after using our formulation in the current and previous experiments (8). In vitro studies revealed a decreased toxicity compared to artesunate (9).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations